PENGARUH BUDAYA KERJA TERHADAP KUALITAS PELAYANAN PERNIKAHAN DI KABUPATEN BANYUMAS - Rosidin; Miyono, Noor (Direktorat Jenderal Bimbingan Masyarakat Islam, 2017)
Work culture is a component of human quality in changing the old way becomes the new way working that is oriented to customer satisfaction or the public. Religious Affairs Office of Banyumas Regency is one of the institutions in charge of services to the community, especially religious and employees implement integrated work culture by the Ministry of Religious Affairs. The purpose of this study to know the work culture influence for the wedding service quality at the Religious Affairs Office of Banyumas, Central Java. The approach used in this study is quantitative. The study population was community service users of the wedding with a sample of 140 obtained with quota purposive random sampling method. The study states: 1) the correlation between the variables work culture and strong service quality with value 0.834; 2) Innovation is an indicator of the weakest in the variable work culture and physical evidence the weakest indicator on service quality variables 3) The amount of influence on a lot of quality work culture of service equal to 69.6% and other variables that affect the quality of service of 30.1%. Workplace culture proven to improve service and provide a significant role, so that the work culture and the employees attached to the Office of Religious Affairs in Banyumas. Kantor Urusan Agama merupakan salah satu institusi yang bertugas melakukan pelayanan kepada masyarakat khususnya bidang keagamaan dan pegawainya menerapkan budaya kerja yang terintegrasi oleh Kementerian Agama. Penelitian ini bertujuan untuk mengatahui pengaruh budaya kerja terhadap kualitas pelayanan pernikahan di Kantor Urusan Agama Kabupaten Banyumas Jawa Tengah. Pendekatan yang digunakan dalam penelitian ini adalah  kuantitatif.  Populasi penelitian adalah masyarakat pengguna jasa layanan pernikahan dengan jumlah sampel 100 yang diperoleh dengan metode kuota purposive random sampling. Hasil penelitian menyatakan : 1) korelasi antara varibel budaya kerja dan kualitas pelayanan kuat dengan nilai 0,834; 2) Inovasi merupakan indikator terlemah pada variabel budaya kerja dan bukti fisik merupakan indikator terlemah pada variabel kualitas pelayanan 3) Besarnya pengaruh budaya kerja terhadap kualitas pelayanan sebesar 69,6 % dan variabel lain yang mempengaruhi kualitas pelayanan sebesar 30,1%. Budaya kerja terbukti meningkatkan pelayanan dan memberikan peran yang signifikan, sehingga budaya kerja melekat pada pegawai dan pelayanan di Kantor Urusan Agama Kabupaten Banyumas.